Anaximander in context new studies in the origins of Greek philosophy (SUNY series in ancient Greek philosophy, 2003)
"Promoting a new, broadly interdisciplinary horizon for future studies in early Greek philosophy, Dirk L. Coupric, Robert Hahn, and Gerard Naddaf establish the cultural context in which Anaximander's thought developed and in which the origins of Greek philosophy unfolded in its earliest stages. In order to better understand Anaximander's achievement, the authors call our attention to the historical, social, political, technological, cosmological, astronomical, and observational contexts of his thought. Anaximander in Context brings to the forefront of modern debates the importance of cultural context, and the indispensability of images to clarify ancient ideologies."--BOOK JACKET.